Effect analysis of percutaneous catheter drainage combined with radiofrequency ablation in the treatment of mixed thyroid nodules - Sun, Wencong; Wang, Yichen; Ding, Chao; Wu, Gang; Zhang, Heng; Su, Zijie; Li, Guoqing (Frontiers in Endocrinology, 2025)
ObjectiveTo compare the efficacy of ultrasound-guided percutaneous catheter drainage in the treatment of cystic thyroid mixed nodules.MethodsA total of 40 patients with cystic mixed thyroid nodules admitted to our hospital were randomly divided into the traditional ablation group (hereinafter referred to as the no-catheter ablation group) and the percutaneous catheter drainage ablation group (20 cases each). The postoperative efficacy of the two groups in the treatment of cystic benign mixed thyroid nodules was compared, including tumor size before and after treatment, treatment duration, pain, hoarseness and recurrence cases.ResultsCompared with the traditional ablation group, the tumor size in the catheter drainage group was significantly reduced, the duration of treatment was shorter, the postoperative pain was lower, the number of hoarseness and tumor recurrence was less (P<0.05).ConclusionFor the treatment of cystic thyroid mixed nodules, percutaneous catheter drainage is more effective than traditional ablation, and the treatment effect is better, the treatment duration is shorter, the postoperative pain is lower, the hoarseness and tumor recurrence cases are less, which is safe and effective. Through clinical study, it is a new and effective treatment method for cystic thyroid mixed nodules, which is worth popularizing.